QS2: Aberrant Breast Adipose Stromal Cell Biology In Women At High Risk For Developing Breast Cancer. (July 2021) - Taskindoust, Mahsa; Xie, Tingjun; Nelson, Valery; Stukes, Bryanna; Hollenbeck, Scott; Bachelder, Robin
Abstract : Purpose: Our laboratory studies contributions of breast adipose stromal cells (bASCs) to breast cancer initiation and progression. To date, most studies of ASC biology have focused on abdominal ASCs. We hypothesize that bASC biology impacts the breast microenvironment in a manner that influences a woman's risk of developing breast cancer. Methods: In order to better understand how aberrant bASC biology contributes to breast cancer, we built a bASC cell repository from women undergoing mastectomies at Duke University Hospital (Duke IRB Pro00100739). Some of these women are at high risk for developing breast cancer. High risk biology includes women with genetic predispositions to cancer, as well as obese and post-menopausal women. bASCs were isolated from the stromal vascular fraction of breast adipose tissue from patients. Additionally, commercially-available ASCs isolated from the abdomen were obtained from Zenbio. Senescence was measured in bASCs using the SPiDER beta gal senescence detection kit (Dojingo). Senescence-associated cytokines were measured in conditioned media collected from these bASCs by ELISA (R&D Systems). The ability of bASCs to differentiate into adipocytes was measured using the Adipo-Red adipocyte differentiation assay (Lonza). Results: To date, we have isolated bASCs from 16 patients undergoing mastectomies at Duke University Hospital. We have studied differences in the biology of these bASCs that may be associated with increased breast cancer risk. A commonality observed in high risk patients was senescence, demonstrated by bASCs undergoing growth arrest and secretion of beta-galactosidase. Similarly, bASCs from high risk patients demonstrated secretion of inflammatory cytokines such as Interleukin-6 (IL-6), Interleukin-8 (IL-8), and Interleukin-1beta (IL-1 beta) that are associated with the senescence-associated secretory phenotype. We hypothesize that the secretion by these bASCs of such cytokines creates an inflammatory breast microenvironment that increases breast cancer risk. Our data also indicate that bASCs from high risk patients exhibit a defect in their ability to differentiate into adipocytes. Conclusion: Our studies are the first to report on a repository of breast ASCs (bASCs) from patients undergoing mastectomies. Results indicate that bASC biology differs significantly amongst patients, with a subset exhibiting a senescent secretory phenotype associated with a block in their ability to differentiate into adipocytes. We hypothesize bASC senescence, associated with a senescence secretory phenotype, results in: 1) the inability of these bASCs to differentiate into adipocytes, and 2) a senescence-associated secretory phenotype that impacts the breast tumor microenvironment. As we continue to build the repository, studies are in progress to test if inflammatory cytokines secreted by senescent bASCs work in a paracrine fashion on breast epithelium to drive breast cancer initiation/ progression.